2020
DOI: 10.1017/jfm.2020.746
|View full text |Cite
|
Sign up to set email alerts
|

Reducing aerofoil–turbulence interaction noise through chordwise-varying porosity

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…2020; Ayton et al. 2021) studies demonstrated the effectiveness of this passive noise-control strategy. However, despite the numerous analyses, the physical mechanisms involved in the noise reduction remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…2020; Ayton et al. 2021) studies demonstrated the effectiveness of this passive noise-control strategy. However, despite the numerous analyses, the physical mechanisms involved in the noise reduction remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, to the authors' best knowledge, the optimization procedure for the design and implementation of a permeable LE is still inconclusive, unlike for LE serrations. In fact, novel permeable LE designs are still being actively investigated at the time of writing [14,15,20,21]. Regardless, these studies have shown that permeable LE applications are very promising in both efficacy and versatility aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Note also that the nature of this boundary condition still permits the time-harmonic form ∼ e −iωt . Previous theoretical [5] and low-fidelity numerical [11] work concerned with the prediction of aerodynamic noise scattering and absorption by porous materials focuses on the first notion of porosity, perforated plates, as these can be easily described by two parameters; the Rayleigh conductivity, K R , and an open area ratio, α, of the surface. Due to the complexity of a background steady flow interacting with a porous material, these models do not include such a background flow and are purely concerned with acoustic scattering.…”
Section: Introductionmentioning
confidence: 99%
“…For further simplicity, the models consider the boundary conditions to be linearised to y = 0, thus effectively reducing an aerofoil to a flat plate. Both semi-infinite and finite plate models have been considered this way [5,11]. Experimental findings show that porosity is effective at reducing low and mid-frequency noise, both for perforations and foam-like materials [4,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation